2006
DOI: 10.1152/jn.01035.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Cold Sensitivity of Two Distinct Populations of TRPM8-Expressing Somatosensory Neurons

Abstract: The cold- and menthol-sensing TRPM8 receptor has been proposed to have both nonnociceptive and nociceptive functions. However, one puzzle is how this single type of receptor may be used by somatosensory neurons to code for two distinct sensory modalities. Using acutely dissociated rat dorsal root ganglion (DRG) neurons without culture, we show that TRPM8 receptors are expressed on two distinct classes of somatosensory neurons. One class is sensitive to menthol and features nonnociceptive neuron properties, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
89
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 34 publications
15
89
1
Order By: Relevance
“…This finding and the higher density of menthol-sensitive currents in LT-CS neurons strongly suggest that they express higher levels of TRPM8. A similar conclusion was reached previously in rat trigeminal and dorsal root ganglion (DRG) (Xing et al, 2006) neurons.…”
Section: Menthol Effects Are Stronger In Low-threshold Cs Neurons Becsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding and the higher density of menthol-sensitive currents in LT-CS neurons strongly suggest that they express higher levels of TRPM8. A similar conclusion was reached previously in rat trigeminal and dorsal root ganglion (DRG) (Xing et al, 2006) neurons.…”
Section: Menthol Effects Are Stronger In Low-threshold Cs Neurons Becsupporting
confidence: 89%
“…In its absence, nociceptor sensory terminals become unexcitable at low temperatures, and it is attractive to speculate that this channel is also expressed by highthreshold cold thermoreceptors. A significant fraction of menthol-and cold-sensitive neurons in DRGs were found to express TTX-resistant sodium channels (Xing et al, 2006). A schematic representation of our proposal is illustrated in supplemental Figure 4, available at www.jneurosci.org as supplemental material.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, TRPV3 continues to respond to painfully hot temperatures (Peier et al 2002b) knockout mice that lack TRPV3 show deficits in response to both noxious and innocuous heat (Moqrich et al 2005). Similarly, the menthol and cold receptor TRPM8 (McKemy et al 2002;Peier et al 2002a), which was recently shown in mice to be the principal receptor for cold below 30°C (Bautista et al 2007;Colburn et al 2007;Dhaka et al 2007;see however Munns et al 2007), has been reported in some DRG and trigeminal ganglion neurons that are capsaicin-sensitive and/or were shown to express TRPV1 (McKemy et al 2002;Okazawa et al 2004;Abe et al 2005;Xing et al 2006;Hjerling-Leffler et al 2007). (See, however, Kobayashi et al 2005.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, functional data from cultured sensory neurons show that approximately one-half of menthol-sensitive neurons are also capsaicinsensitive, suggesting coexpression of both TRPM8 and TRPV1 in this subset of cold-and menthol-sensitive neurons (McKemy et al, 2002;Viana et al, 2002;Hjerling-Leffler et al, 2007). Last, in primary culture, a subset of menthol-sensitive DRG neurons has been shown to have nociceptive properties (Xing et al, 2006). Thus, we examined coexpression of GFP and TRPV1 immunoreactivity in TG and DRG and, consistent with functional data, found that 38.8 Ϯ 2.2% (n ϭ 719) and 23.7 Ϯ 4.6% (n ϭ 221) of GFP ϩ TG and DRG soma also express TRPV1, respectively (Fig.…”
Section: Trpm8 Is Expressed In Both Nociceptive and Non-nociceptive Smentioning
confidence: 97%